2016
DOI: 10.1523/jneurosci.3474-15.2016
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxymethylation of microRNA-365-3p Regulates Nociceptive Behaviors via Kcnh2

Abstract: DNA 5-hydroxylmethylcytosine (5hmC) catalyzed by ten-eleven translocation methylcytosine dioxygenase (TET) occurs abundantly in neurons of mammals. However, the in vivo causal link between TET dysregulation and nociceptive modulation has not been established. Here, we found that spinal TET1 and TET3 were significantly increased in the model of formalin-induced acute inflammatory pain, which was accompanied with the augment of genome-wide 5hmC content in spinal cord. Knockdown of spinal TET1 or TET3 alleviated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
59
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(59 citation statements)
references
References 78 publications
0
59
0
Order By: Relevance
“…Recently, Alarcon and colleagues demonstrated that m 6 A modification could mark pri-miRNA for processing by recognizing DGCR8 in a METTL3-dependent manner, 18 indicating that altered METTL3-mediated m 6 A modification might be responsible for the aberrant expression of miRNAs in many biological processes. 21 It is possible that miR-365-3p is targeted by two different regulators during inflammatory pain condition. We found that increased METTL3 induced by CFA could regulate pri-miRNA-365-3p processing in an m 6 A-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Alarcon and colleagues demonstrated that m 6 A modification could mark pri-miRNA for processing by recognizing DGCR8 in a METTL3-dependent manner, 18 indicating that altered METTL3-mediated m 6 A modification might be responsible for the aberrant expression of miRNAs in many biological processes. 21 It is possible that miR-365-3p is targeted by two different regulators during inflammatory pain condition. We found that increased METTL3 induced by CFA could regulate pri-miRNA-365-3p processing in an m 6 A-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies revealed that 5hmC is consistently found at significantly reduced levels (more than 50% reduction, p ≤ 0.01) in various solid tumors (73)(74)(75). Recently, using a mouse model, Pan et al (76) studied the role of hydroxymethylation in neurophysiological processes and provided the first evidence that miRNAs can be regulated by hydroxymethylation of their promoters. Working with a mouse model of formalin-induced acute inflammatory pain, they observed a significant increase in 5hmC and a decrease in 5mC in the miR-365-3p promoter that resulted in the enhancement of miR-365-3p transcription and in the subsequent increase of miR-365-3p expression (Figure 4).…”
Section: Dna Hydroxymethylationmentioning
confidence: 99%
“…Conversely, Tet1-knockout mice present learning deficiencies and memory retention accompanied by extensive methylation of cytosine in the promoters of learning/memory-related genes8. Recently, a study reported that spinal Tet family are essential for inflammatory nociception transmission9. These evidence implying that analogous forms of synaptic plasticity caused by the Tet1-mediated DNA demethylation-modifying 5 mC/5 hmC enrichment in pain-associated genes may operate at spinal sites to participate in neuropathic pain processing.…”
mentioning
confidence: 99%